Workplace Harassment And Perception Of Organizational Support On Turnover Intention: Job Satisfaction As A Mediation Variable - Diva Luthfianti Mukaromah; Vitradesie Noekent; Zhou Wanbing (Journal of Management and Business Insight, 2023)
Purpose-This study looks at job satisfaction as a mediating variable to explore the relationship between workplace harassment and perceived of organizational support on intention to leave. Design/Methodology/Approach-Employees in the textile and textile products sector in Central Java Province made up the study's population. Purposive sampling was used to acquire the data for this study, and a total of 60 participants made up the sample. Through the use of an analytical program called Smart PLS version 3.0, the outer model and inner model analysis methods were used to analyze the data for this study. Findings-The direct findings demonstrated that job satisfaction and turnover intention were highly impacted by workplace harassment and perceptions of organizational support. Job satisfaction did, however, have a negative and negligible effect on the intention to leave. The indirect findings indicated that there was no evidence to support the idea that job satisfaction could moderate the effects of workplace harassment on intention to leave and the perception of organizational support on intention to leave. Research limitations/implications-These findings have policy implications for all levels of government in Central Java Province, which must prioritize reducing workplace harassment through strict enforcement of regulations. For companies, the results of this research can be used to develop perceived organizational support programs. Originality/value-The study on employee behaviour in the textile products business is quite restricted, and no earlier studies on the influence of workplace harassment and perceived organizational support on turnover intention mediated by job satisfaction have been done. This study also calls into question the widely held belief that findings collected in one specific location may be extended to the larger phenomena at the country level.